HUBUNGAN KESEPIAN DENGAN SMARTPHONE ADDICTION PADA MAHASISWA MERANTAU DI UNIVERSITAS NEGERI PADANG - Aulia, Fitri Salsabilla Nurul; Fikry, Zulian (Innovative: Journal Of Social Science Research, 2025)
This study aims to determine how the relationship between loneliness and smartphone addiction in overseas students at Padang State University. The research method used is quantitative correlation using accidental sampling as a sampling technique. The number of samples in this study were 156 overseas students at Padang State University. The measuring instrument used in this study is the smartphone addiction scale from Daulay (2023) which adapts the Smartphone Addiction Scale Development And Validation Of A Short Version For Adolescent from Kwon et al. (2013) and the loneliness scale from Maharani (2024) which adapts the measuring instrument from A Rasch Type Loneliness Scale from (Gierveld & Tilburg, 2006). The data analysis technique used is Pearson's Product Moment correlation with the support of the SPSS program version 26.0 for Windows. The results showed that there is a unidirectional positive relationship between loneliness and smartphone addiction in students who migrate at Padang State University with a low correlation value of 23% (r = 0.237; p = 0.003) which means that the higher the loneliness experienced by students migrating, the higher the smartphone addiction in students, and vice versa. The results showed that the alternative hypothesis (Ha) was accepted, which means that there is a significant positive relationship between loneliness and smartphone addiction in overseas students at Padang State University.